2000
DOI: 10.1300/j019v22n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Similarity and Children with Attention-Deficit/Hyperactivity Disorder

Abstract: ABSTRACT. This study examined the relation between parenting similarity and comorbid internalizing and disruptive behavior problems among 70 children with Attention-Deficit/Hyperactivity Disorder (ADHD). General child rearing similarity and discipline similarity were found to be associated with fewer disruptive behavior problems but not related to internalizing problems. Parenting similarity was also found to be associated with greater marital adjustment and less marital conflict among parents of ADHD children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
1
23
0
3
Order By: Relevance
“…Parenting dissimilarities may also affect parents' satisfaction with their parenting roles if they lead to frequent and stressful disagreements about handling childrearing problems (Harvey, 2000). This may partly explain the level of parenting dissatisfaction expressed by both parents of the hyperactive group boys in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…Parenting dissimilarities may also affect parents' satisfaction with their parenting roles if they lead to frequent and stressful disagreements about handling childrearing problems (Harvey, 2000). This may partly explain the level of parenting dissatisfaction expressed by both parents of the hyperactive group boys in the present study.…”
Section: Discussionmentioning
confidence: 78%
“…It has also been reported that families of hyperactive children were twice as likely to have received family therapy as they reported relatively higher incidence of marital dysfunction (Befera and Barkley, ). The parents are likely to experience less alliance, more dissatisfaction and fighting with their spouse than the control group (Harvey, ). Barkley et al .…”
Section: Discussionmentioning
confidence: 99%
“…In her study of conduct-problem children, Webster-Stratton (1985a) found that when fathers and mothers were involved in parent training, mother-child interactions were less negative than when fathers were absent from the therapeutic process. In another investigation, parenting similarities between mothers and fathers (i.e., fathers' reports of parenting alliance and discipline similarity) were found to be associated with lower parenting stress for mothers (Harvey, 2000). Another benefit of including fathers in child-oriented treatment is that this may help uncover underlying difficulties that might have been missed when focusing solely on mothers and children (Prevatt, 1999).…”
Section: Therapeutic Benefits Related To Fathers' Inclusion In Treatmentmentioning
confidence: 99%